Formulation and In Vitro Evaluation of Fast Disintegrating Tablets of an Anti-Inflammatory Drug using Natural Super Disintegrating Agens: Pharmaceutical Sciences-Pharmaceutics for better Drug formulation - Chinthaginjala, Haranath; Ahad, Hindustan Abdul; Samhitharao, Bitrganti; Yasaswini, Vangala Sai; Madana, Gowthami; Varam, Naga Jyothi; Dasari, Rahulraghav (International Journal of Life Science and Pharma Research, 2021)
Fast disintegrating tablets are defined as solid dosage forms containing medicinal substances which disintegrate rapidly usually within seconds when placed upon the tongue. The present work is concerned with the formulation and in vitro evaluation of fast disintegrating tablets of an inflammatory drug using natural super disintegrating agents like jackfruit seed powder and oats powder. The objective of this study was to develop the aceclofenac tablets with rapid disintegration employing natural super disintegrants and to enhance the patient compliance by providing rapid therapy in the inflammation conditions. Natural super disintegrants were employed in the study as they are devoid of toxic effects. The tablets were prepared by direct compression method. Ten formulations were developed with different concentrations (2%, 4%, 6%, 8%, 10%) of natural disintegrants like jackfruit seed powder and oats powder. FTIR and DSC studies showed no evidence of interaction of drugs with natural super disintegrating agents and other excipients. Precompression parameters were evaluated for all the formulations and were in the acceptance limits. The results of flow properties such as angle of repose, carr’s index and hausners ratio ensured that all the formulations exhibited good flow. Post compression parameters like hardness, friability, disintegration test and dissolution test were evaluated. Among all the formulations, tablets developed using jackfruit seed powder showed best results with respect to disintegration and drug release. The in vitro drug release profile shows that formulation F5 which contains jack fruit seed powder exhibited 98.7% of drug release at the end of 30 min and the disintegration time was found to be 32 seconds. The drug release from F5 formulation follows first order kinetics. F5 formulation is considered as the promising formulation which ensures the patient compliance by providing rapid disintegration.